Postmeister und Stationsaufseher Eine Studie zur deutschen Puškin-Rezeption. - Schneider, Martin (Vortraege und Abhandlungen zur Slavistik, 1997)
The study will be published on the 160th anniversary of the death of Aleksandr Puškin and in the run-up to the big jubilee in 1999. Its purpose is to shed light on a chapter in German-Russian cultural history and to point out the connecting and the dividing.